Effects of carbon-nanotube and lime on the weak soil stability - Al-Mansob, Ramez Al-Ezzi Abduljalil; Lim, Yi Jia; Alsharef, Jamal; Jassam, Taha; Jing, Lin Ng; Ali, Shaban; Surol, Salihah (American Institute of Physics Inc., 2021)
Weak soil causing problem in pavement, landslide and fallen of building due to the low mechanical strength and the high shrinkage properties characteristic. But mixing weak soil with filler could improve the soil properties. The mixing of lime with weak soil and lime mix with nanotube and soil could improve the weak soil mechanical properties. The aim of this study is to show the improvement of unconfined compressive strength of weak soil after adding lime and nanotube and curing for 0, 7, 14 and 28 days of curing period. For the modification of soil in this study was using the lime and nanotube to mix with weak soil. The modified soil has been gone through the curing process for 0, 7, 14 and 28 days. The unconfined compressive strength of treated soil was increases when stabilizer content increases. Especially, that containing 0.1% of carbon-nanotube content and 5% of lime with 28 days of curing period could achieve 1.5 times higher than untreated sample. The improvement in the mixing content process including the pozzolanic process and the flocculation process which reduce the void between the soil particle. Hence increase the mechanical strength and unconfined compressive strength of treated soil. This economical treatment can contribute to construction by reducing the differential settlement and increase the strength of subgrade in pavements.